METODE PERMAINAN PUZZLE UNTUK MENDORONG KEAKTIFAN SISWA DI KELAS - Mega Irma Wati; Kutratul Yuyun; Fadil; Anang Sumarno (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Active learning is an approach that places students at the center of the learning process through direct involvement in various activities. The teacher acts as a facilitator who builds effective communication so that the class atmosphere becomes interactive and encourages students to be more active. Student activity makes an important contribution to understanding the material and improving learning outcomes. Game methods, especially puzzles, are strategies that support the implementation of active learning. Puzzles make the learning process more interesting while training students' critical thinking, concentration, creativity and collaboration skills. Challenges in puzzles increase motivation and encourage student participation in learning activities. Based on studies conducted, the use of puzzles has proven to be effective in increasing the activity, motivation and learning outcomes of elementary school students. In this way, puzzles can be used as an innovative learning medium that is able to create an interactive and fun learning atmosphere.